Parenting Style and Cyber-Aggression in Chinese Youth: The Role of Moral Disengagement and Moral Identity - Zhang, Yizhi; Chen, Cheng; Teng, Zhaojun; Guo, Cheng (Frontiers in Psychology, 2021)
Previous research has shown that parenting style is intricately linked to cyber-aggression. However, the underlying mechanisms of this relationship remain unclear, especially among young adults. Guided by the social cognitive theory and the ecological system theory, this study aimed to examine the effect of parenting style on cyber-aggression, the potential mediating role of moral disengagement, and the moderating role of moral identity in this relationship. Participants comprised 1,796 Chinese college students who anonymously completed questionnaires on parenting style, moral disengagement, moral identity, cyber-aggression, and demographic variables. After controlling for sex and age, both parental rejection and over-protection were positively related with participants’ cyber-aggression; nonetheless, parental emotional warmth was non-significantly related with cyber-aggression. Mediation analysis revealed that parenting style was related to cyber-aggressive behavior through moral disengagement. Moderated mediation analysis further indicated that the indirect effect of parenting style on cyber-aggression was much stronger in college students with higher moral identity. The study carries important practical implications for parents and educators concerned about the destructive consequences of cyber-aggression.